Cost-effectiveness of drug-eluting stents versus bare-metal stents in patients undergoing percutaneous coronary intervention (2012)
Objective To describe the initial experience with direct implantation of a CoreValveTM selfexpanding aortic valve prosthesis in a tertiary cardiovascular care center from Argentina. Methods From May to December 2010, 21 consecutive patients with severe aortic stenosis (SAS) and high surgical riskwere included to undergo percutaneous aortic valve replacement with a CoreValveTM prosthesis. The inclusion criteria were the following: aortic valve area <1 cm2 (<0.6 cm2/m2); aortic annulus diameter of 20- 27 mm; ascending aorta diameterat the level of the sinotubular junction ≤ 40 (small prosthesis) or ≤ 43 mm (large prosthesis), and femoral artery diameter >6 mm.